Personal initiative: Its power in social entrepreneurial venture creation - Isa Nsereko; Waswa Balunywa; John Munene; Laura Orobia; Ngoma Muhammed (Cogent Business & Management, 2018)
Social entrepreneurship literature bears a positive cast on poverty reduction and social problem-solving. Studies have shown that social entrepreneurial venture activities have far-reaching socioeconomic impact, especially in solving societal challenges. We argue that given the nature of social problems, certain personality traits are valuable. Individuals with personal initiative are capable of using their prior knowledge, proactive and innovative and experience to be alert as they create social ventures that create social impact. The study examined the role of personal initiative in social entrepreneurial venture creation among Community-Based Organizations (CBO) in a developing country. Scholars have examined a number of psychological traits underlying Social Entrepreneurial Venture Creation but less emphasis has been laid on the role of personal initiative in creating social entrepreneurial ventures. We used a sample of 243 Kampala Capital City Authority CBO owners and the results indicate that personal initiative in terms of proactiveness and innovation is positively and significantly associated with social entrepreneurial venture creation.
Keywords: 650